Creative clusters in Europe: a microdata approach - Rafael Boix Domenech; Luciana Lazzeretti; José Luis Hervàs Oliver; Blanca De Miguel Molina; Borja Trujillo Ruiz (European Regional Science Association (ERSA), 2011)
Creative industries are highly concentrated forming clusters. One of the main problems for the identification of clusters of creative industries in Europe is the lack of data, constrained in practice to regions (NUTS 2) and influenced by the heterogeneity in the definition of NUTS across countries. This research uses firm-level data geo-referenced at address level and geostatistical modeling to identify clusters of creative industries in fifteen European countries. The procedure is independent of administrative divisions and national boundaries and allows to produce a precise geography of the clusters of creative industries in Europe.
Keywords: 330